TO THE 100TH ANNIVERSARY OF THE BIRTH ALYSHBAEV DZHUMAGUL ALYSHBAEVICH ACADEMICIAN OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, DOCTOR OF ECONOMIC SCIENCES, PROFESSOR (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
0